Preparation and characterization of ZnS nanoparticles synthesized from chitosan laurate micellar solution - Khiew, P.S.; Radiman, S.; Huang, N.M.; Soot Ahmad, M.; Nadarajah, K. (2005)
Synthesis of ZnS nanostructured materials has been performed in the micellar solution system, containing chitosan laurate as the surfactant. The self-assembling of the surfactant molecules in water solution can form unique architecture that can be adopted as the reaction template for the formation of nanomaterials. The synthesized nanomaterials have been characterized by energy filter transmission electron microscopy (EFTEM), Energy Dispersive X-ray Analysis (EDAX), X-ray diffractometry (XRD) and UV-Visible absorption measurement in order to determine the size, morphology, composition, crystal structure and optical behavior of the products. The spectroscopic results showed that the synthesized nanoparticles exhibited strong quantum confinement effect as the optical band gap increased significantly as compared to the bulk materials. In addition, the size of the resulting nanoparticles is greatly affected by the surfactant concentration and range from 2 to 10 nm. It was found that the nanomaterials obtained existed in face-centered cubic structure and exhibited the characteristic line broadening feature in the XRD patterns. Â© 2004 Elsevier B.V. All rights reserved.